Perlindungan Hukum Terhadap Tenaga Kerja Yang Mengalami Pemutusan Hubungan Kerja Sepihak - Sitabuana, Tundjung Herning; Clarosa, Vivian; Lie, Cathleen; Retaly, Andrea Tamaranova; Armando, Very (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to find out how the law protects workers affected by layoffs unilaterally. Termination of employment (PHK) unilaterally should not be carried out because only one party benefits and the other party feels disadvantaged. Therefore, there are problems that result in the end of the rights and obligations of workers and employers regulated in Law Number 13 of 2003 concerning Manpower. It doesn't work, sometimes there are disputes. This usually happens because there is no common understanding between workers/employees and employers. Termination of employment can be resolved bilaterally, conciliation, arbitration and industry-related courts.Basically Termination of Employment (PHK) unilaterally is a decision made by a company without going through a legal process or the establishment of an Industrial Relations Dispute Settlement Institution. There is also disagreement about the legal basis for Termination of Employment (PHK) in which a company can terminate unilaterally for 2 (two) reasons, namely, the first is due to dismissal for the same reason in the worker/employee and the second is dismissal for the same reason in company. The research uses normative legal research methods with a statutory approach accompanied by primary and secondary legal materials